К улучшению качественных харктеристик металла шва сварных соединений паропроводов - Дмитрик, Виталий Владимирович; Лучка, Н. В.; Скляр, О. В. (НТУ "ХПИ", 2012)
Изучена возможность улучшения качественных характеристик исходной структуры сварных соединений из теплоустойчивых перлитных сталей путем использования процесса механизированной сварки в смеси защитных газов CO2+Ar

The possibility of improving the qualitative characteristics of the original structure of welded joints of heat-resistant pearlitic steels by the use of mechanized welding process in the shielding gas mixture of CO2 + Ar
Тo improve quality kharakteristik weld metal welds steam welds to improvement of high-quality kharkteristik of metal of guy-sutures of the weld-fabricated connections of paroprovodov
Keywords: перлитные стали; теплоустойчивость; защитные газы; излом; электродная проволока; сегрегация